Digital Transformation and Sustainable Local Tax System Practices in Emerging Market: A Qualitative Analysis - Zulfiqar, Faisal Labib; Silvia, Tiffani; Abrori, Ali (Journal of Advances in Accounting, Economics, and Management, 2024)
The Covid-19 pandemic has forced regional governments to adapt in providing services, including in terms of taxation. This study deals with the introduction of the electronic Notification of Tax Due of Land and Building Tax at the Unit X, one of the subnational tax office in Jakarta. In a bid to enhance the efficiency, effectiveness and convenience of the processes, and also promote eco-friendliness through paperless practice, the transition from paper-based processes to computerized ones was undertaken. Emphasizing on the electronic Notification of Tax Due system as per Governor Regulation No. 23 of 2021, the system enabled taxpayers to access tax documents as they were uploaded in the electronic platforms and this enhanced the reliability of the notifications while ease the burden of paperwork. The research employed interviews, observations and document analysis of the electronic Notification of Tax Due implementation and found that the emerging system improved the convenience of taxpayers through quick service delivery but also enhanced service quality in a green economy line with SDGs 12, 13 and 15. Nonetheless, the findings revealed a digital divide particularly among the seniors and the economically disadvantaged which calls for the integration of digital literacy policies targeting those groups. Nevertheless, the electronic Notification of Tax Due system stands as a testament the opportunities available in embracing technology in the provision of services, enhancement of sustainability and the involvement of the citizens in the management of a city.